THE GENERAL THEORY OF TEACHING A FOREIGN LANGUAGE IS CALLED LINGUISTICS (LINGUODIDACTICS). - Durdona Bahodirovna Boltayeva (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
This article explores the concept of linguodidactics as a comprehensive framework for foreign language teaching. It looks at the theoretical foundations of linguodidactics and highlights how it integrates pedagogical practice and linguistic theory. With an emphasis on the interaction of language structure, cognitive processes, and cultural context, the conversation focuses on important ideas, approaches, and tactics that improve language acquisition. The article seeks to give teachers insights into successful teaching strategies that promote student engagement and proficiency by examining modern approaches and their implications for curriculum design and classroom instruction. In the end, it makes the argument that linguodidactics is an essential tool for creating a coherent and engaging foreign language teaching approach.